Reading Texts as Bodies: Object Agency in the Age of Human Empowerment - Zürn, Tobias Benedikt (Method & theory in the study of religion, 2025)
We scholars tend to project discursive approaches and anthropocentric orientations based on our own reading habits onto the writings we study. This tendentious attitude repeatedly leads to misunderstandings and mistranslations of texts produced in communities that do not share our inclination towards these writings. I illustrate this danger by introducing the case of the Huainanzi. This massive and extraordinarily constructed classic from the second century BCE is commonly read as an encyclopedia that contains various philosophical treatises about sage rulership. I show that this standard interpretation is neither based on the Huainanzi’s self-reflexive comments nor on the illustrations of its earliest commentator, since both depict the classic as a powerful embodiment of the Dao that orders the world via resonances. Hence, my essay reminds us that we run the risk of falsely attributing the powers people sometimes attributed to textual bodies like the Huainanzi to human beings if we are inattentive to the cultural situatedness of our own reading habits.